Multiplex imaging analysis of the tumor immune microenvironment for guiding precision immunotherapy - Liu, Feng; Li, Guiqing; Zheng, Yi; Liu, Yanxia; Liu, Kang (Frontiers in Immunology, 2025)
Cutting-edge multiplex imaging technologies have significantly advanced our understanding of the tumor immune microenvironment (TIME), delivering nanometer-scale spatial resolution that illuminates previously inaccessible cellular interactions and organizational patterns. This mini-review discusses the latest multiplex imaging methods, including Imaging Mass Cytometry (IMC), Multiplexed Ion Beam Imaging (MIBI), Cyclic Immunofluorescence (CycIF), and Digital Spatial Profiling (DSP), emphasizing their roles in identifying spatial immune signatures predictive of immunotherapy responses. Clinical applications across various cancers—such as NSCLC, melanoma, breast cancer, colorectal cancer, and hepatocellular carcinoma—highlight how spatially resolved immune profiles can enhance patient stratification and treatment personalization. Notably, increased CD8+ T cell density and spatial colocalization with tumor cells have been broadly correlated with improved immunotherapy response and survival across multiple cancer types. Despite current technical and analytical challenges, ongoing technological advancements and integration with emerging methods like spatial transcriptomics and super-resolution imaging promise broader clinical utility, ultimately improving patient outcomes in precision immunotherapy.